About some features of authorship in a music video project - Shemiakina, Elena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. In contemporary music the search for new screen forms of presentation of music pieces to the general public is constantly happening, featuring innovation technologies (television, computer). Within this framework we can speak about a certain musical genre trend that is represented by art music documentary with a concert presentation, music video, and music video project, etc. Main objective of the study. The article considers phenomenon of authorship in one of the modern forms of video presentation of a musical work that was called ‘musical video project.’ In this form video images shown on the screen are added to the sound of traditional performance of the music piece, and this should promote an effective music message reach the mainstream audience. Methodology of the study. The main method was the analysis and research, as well as the synthesis, which allowed to combine different types of creative activity in the whole direction of the mid 20–21 century. Results and conclusions. The main participants of artistic activity here, as well as in traditional forms of musical presentation, remain the composer and musician. But at the same time another category of performers works, the number of which varies. Those may be video makers, sound and video directors, technical staff and other participants. To illustrate the expansion of the functions of authorship we give an example of a large-scale American video project located in Miami in a specially constructed New World Center architectural complex. The author of the entire architectural solution, built based on the principle of openness, is a famous American architect Frank Owen Gehry. We analyze features of the Sun Trust Pavilion concert hall where video projects take place. The author of the video footage is the famous artist Tal Posner, who relies in his video images on graphic structure and music style. The video footage is shown along with the music tempo– rhythm. The initiator and one of the leading participants of video projects is a famous American conductor Michael Tilson Thomas. The music is performed by the specially created New World Symphony Orchestra.